Food and culture - Kittler, Pamela Goyan; Sucher, Kathryn P. (Australia : Thomson Wadsworth, 2008)
Provides information on the health, culture, food, and nutrition habits of the most common ethnic and racial groups living in the United States. This book helps health professionals, chefs, and others in the food service industry to learn to work effectively with members of different ethnic and religious groups in a culturally sensitive manner.
1. Food and Culture -- 2. Traditional Health Beliefs and Practices -- 3. Intercultural Communication -- 4. Food and Religion -- 5. Native Americans -- 6. Northern and Southern Europeans -- 7. Central Europeans, People of the Former Soviet Union, and Scandinavians -- 8. Africans -- 9. Mexicans and Central Americans -- 10. Caribbean Islanders and South Americans -- 11. Chinese, Japanese, and Koreans -- 12. Southeast Asians and Pacific Islanders -- 13. People of the Balkans and the Middle East -- 14. Asian Indians and Pakistanis -- 15. Regional Americans.
Includes bibliographical references and index.
Keywords: NUTRITION -- UNITED STATES -- CROSS CULTURAL STUDIES